Kompetensi Fasilitator Pelatihan Pusat Pengembangan dan Pemberdayaan, Pendidik dan Tenaga Kependidikan Pertanian (P4TK Pertanian) Kementerian Pendidikan dan Kebudayaan - Eko Warisdiono; Ma’mun Sarma; Darwis S Gani; Djoko Susanto (Jurnal Penyuluhan, 2013)
The success of the training execution one other is determined by facilitator competency. Therefore facilitator is strived to havecompetency in implementing learning task suitable with the wish and need of training participants. The aims of this researchis to analyse factors dominantly influencing competency of facilitators of P4TK Pertanian Cianjur. This research is conductedin P4TK Pertanian Cianjur, using P4TK fasilitators as respondents. The research is carried out in P4TK Pertanian Cianjurusing 121 facilitators by census. Reserch result showed that most part of the facilitators master the competence in the level ofmedium. Factors that significantly influencing positively the competence of the facilitators are involvement of facilitators inlearning process, motivation, and working environment. Meanwhile the individual characteristics does not significantly influencefacilitator competency.Keywords: training, facilitator, competency